A Review of the Molecular Aggregation of Small-Molecule Anion Sensors for Environmental Contaminates in Aqueous Media - Mallory E. Thomas; Alistair J. Lees (Sustainable Chemistry, 2025)
A primary challenge in the further development of anion sensors in real water samples of environmental concern is the need for highly water-soluble compounds that are able to detect low concentrations of analytes. Small-molecule sensors can mitigate solubility constraints and highly aromatic or conjugated systems may provide a new way to recognize target analytes with high sensitivity and/or selectivity. Organic aggregates that have the ability to form large frameworks can exhibit aggregated-induced emissions to detect target analytes, and their coagulation can provide enhanced detection via colorimetric or fluorescent measurements. This review aims to draw attention to the emerging area of small-molecule organic chemosensors that utilize aggregation to detect environmentally detrimental anions in an aqueous solution. A number of mechanisms of interaction for anion recognition are recognized and discussed here, including electrostatic interactions, covalent bond formation, hydrophobic interactions, and even complexation.